Pathogenesis of Nonalcoholic Steatohepatitis and Hormone-Based Therapeutic Approaches - Kim, Kook Hwan; Lee, Myung-Shik (Frontiers in Endocrinology, 2018)
Non-alcoholic fatty liver disease (NAFLD) is an emerging global health problem and a potential risk factor for type 2 diabetes, cardiovascular disease, and chronic kidney disease. Nonalcoholic steatohepatitis (NASH), an advanced form of NAFLD, is a predisposing factor for development of cirrhosis and hepatocellular carcinoma. The increasing prevalence of NASH emphasizes the need for novel therapeutic approaches. Although therapeutic drugs against NASH are not yet available, fundamental insights into the pathogenesis of NASH have been made during the past few decades. Multiple therapeutic strategies have been developed and are currently being explored in clinical trials or preclinical testing. The pathogenesis of NASH involves multiple intracellular/extracellular events in various cell types in the liver or crosstalk events between the liver and other organs. Here, we review current findings and knowledge regarding the pathogenesis of NASH, focusing on the most recent advances. We also highlight hormone-based therapeutic approaches for treatment of NASH.